INTELLECTUAL CULTURE AS A COMPONENT OF TEACHER'S PROFESSIONAL COMPETENCE (Pedagogy of Higher and Secondary Education, 2022)
In clause problems of formation of intellectual culnre of the person are considered. The anahsk of concept "intelligence", "intellectual cuiture" is submitted. The intellectual culture of the person is formed during all life. The intellectual culnure depends and simultaneously influences developmeni of all specific subsystems of the personal culture connected among themselves.
Keywords: intelligence; intellectual culture